Structure of African Populations of Pyricularia oryzae from Rice - (:unkn) unknown (My University, 2021)
Rice blast, caused by the filamentous ascomycete Pyricularia oryzae, is one of the most devastating diseases of rice. Four genetic clusters were previously identified, and three have a large geographic distribution. Asia is the center of diversity and the origin of most migrations to other continents, and sexual reproduction persisted only in the South China-Laos-North Thailand region, which was identified as the putative center of origin of all P. oryzae populations on rice. Despite the importance of rice blast disease, little is known about the diversity and the population structure of the pathogen in Africa (including Madagascar). The present study was intended to describe the structure of African populations of P. oryzae and identify the relationship between African and worldwide genetic clusters. A set of 2,057 strains (937 African and 1,120 Madagascan strains) were genotyped with 12 simple sequence repeat markers to assess the diversity and the population structure of P. oryzae. Four genetic clusters were identified in Africa and Madagascar. All four clusters previously identified are present in Africa. Populations from West Africa, East Africa, and Madagascar are highly differentiated. The geographic structure is consistent with limited dispersion and with some migration events between neighboring countries. The two mating types are present in Africa with a dominance of Mat1.2, but no female-fertile strain was detected, supporting the absence of sexual reproduction on this continent. This study showed an unsuspected high level of genetic diversity of P. oryzae in Africa and suggested several independent introductions.
Keywords: African Research